2021
DOI: 10.3389/fimmu.2021.730471
|View full text |Cite
|
Sign up to set email alerts
|

Engineering an Antibody V Gene-Selective Vaccine

Abstract: The ligand-binding surface of the B cell receptor (BCR) is formed by encoded and non-encoded antigen complementarity determining regions (CDRs). Genetically reproducible or ‘public’ antibodies can arise when the encoded CDRs play deterministic roles in antigen recognition, notably within human broadly neutralizing antibodies against HIV and influenza virus. We sought to exploit this by engineering virus-like-particle (VLP) vaccines that harbor multivalent affinity against gene-encoded moieties of the BCR antig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 94 publications
2
5
0
Order By: Relevance
“…Despite this 4-fold difference in affinity, we observed comparable total BCR signaling relative to the IgM control for all functionalized DNA-VLPs, consistent with previously described avidity effects at the B-cell surface 61 . We concluded that our DNA-VLPs efficiently interacted with and induced signaling by RBD-specific BCRs, analogous to previous studies using similar assays to evaluate multivalent subunit vaccines 58,[62][63][64][65][66][67][68] . The increased B-cell activation for I52-30x-RBD contrasts our previous findings for HIV antigens for which total Ca 2+ flux saturated beyond a valency of 10x 48 .…”
Section: Resultssupporting
confidence: 83%
“…Despite this 4-fold difference in affinity, we observed comparable total BCR signaling relative to the IgM control for all functionalized DNA-VLPs, consistent with previously described avidity effects at the B-cell surface 61 . We concluded that our DNA-VLPs efficiently interacted with and induced signaling by RBD-specific BCRs, analogous to previous studies using similar assays to evaluate multivalent subunit vaccines 58,[62][63][64][65][66][67][68] . The increased B-cell activation for I52-30x-RBD contrasts our previous findings for HIV antigens for which total Ca 2+ flux saturated beyond a valency of 10x 48 .…”
Section: Resultssupporting
confidence: 83%
“…Despite this four-fold difference in affinity, we observed comparable total BCR signaling relative to the IgM control for all functionalized DNA-VLPs, consistent with previously described avidity effects at the B cell surface 63 . We conclude that our DNA-VLPs efficiently bound and induced signaling by RBD-specific BCRs in a valency-dependent manner, analogous to studies using similar assays to evaluate protein-and DNA-scaffolded multivalent subunit vaccines 53,61,[64][65][66][67][68][69][70] .…”
Section: Dna-vlps Elicit Valency-dependent B Cell Signaling In Vitrosupporting
confidence: 53%
“…The B cell activation assay was adapted from previously established protocols 61 , 69 , 98 . Briefly, the human anti-RBD antibodies CR3022 59 and B38 62 were expressed as IgM B cell receptors (BCRs) in Ramos B cells after lentiviral transfection of the corresponding light chain and transmembrane IgM heavy chain genes.…”
Section: Methodsmentioning
confidence: 99%
“…The HC2 mice are an established transgenic model in which human V H gene usage is constrained to user-defined gene segments, while allowing for recombination with diverse human D and J segments, generating an antibody CDRH3 repertoire that is similar to humans and which supports affinity matured antibodies following immunization with protein antigens 47 52 . HC2 mice using the human V H gene IGHV1-2*02 were deployed in which LC input was from the mouse repertoire 47 , 50 52 . The HC2 mice were a gift to D.L.…”
Section: Methodsmentioning
confidence: 99%